Maladaptive Beliefs as a Mediator Between Trauma and Anxiety in Adult Survivors - Maisarah, Syarifah; Chen, Mei-Ling (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to examine the mediating role of maladaptive beliefs in the relationship between trauma exposure and anxiety symptoms in adult survivors. Methods and Materials: A descriptive correlational design was employed with a sample of 430 adult participants from Taiwan, selected based on Krejcie and Morgan’s sample size table. Participants completed the Life Events Checklist for DSM-5 (LEC-5) to assess trauma exposure, the Posttraumatic Cognitions Inventory (PTCI) to measure maladaptive beliefs, and the Beck Anxiety Inventory (BAI) to evaluate anxiety symptoms. Descriptive statistics and Pearson correlation analyses were performed using SPSS-27 to examine bivariate relationships, while Structural Equation Modeling (SEM) was conducted in AMOS-21 to assess the direct, indirect, and total effects among the study variables and to test the model’s fit. Findings: The results showed significant positive correlations between trauma and maladaptive beliefs (r = .51, p < .001), trauma and anxiety (r = .46, p < .001), and maladaptive beliefs and anxiety (r = .62, p < .001). SEM analysis indicated that maladaptive beliefs significantly mediated the relationship between trauma and anxiety. The direct path from trauma to anxiety (β = .26, p < .001), the path from trauma to maladaptive beliefs (β = .51, p < .001), and the path from maladaptive beliefs to anxiety (β = .48, p < .001) were all statistically significant. The indirect effect of trauma on anxiety through maladaptive beliefs (β = .25, p < .001) confirmed partial mediation. Model fit indices indicated a good fit (χ²/df = 2.41, CFI = 0.98, RMSEA = 0.057). Conclusion: Addressing these dysfunctional cognitions may be essential for reducing anxiety symptoms and improving trauma recovery outcomes.